Evaluation of colony-stimulating factor 1 in invasive breast carcinoma and its association with prognostic parameters - Ahmad Affandi, Khairunisa; Sediqi, Mohammad Faiq; A Talib, Noorlelawati; Muhammad, Naznin; Che Alhadi, Shahidah; Abdullah, Suhaila (2022)
Introduction: There were 2.1 million new cases of breast cancer in 2018 worldwide.About 60-75% of breast cancers are of invasive carcinoma of no special type (NST). Recent cancer research has focused on tumour microenvironment (TME) and the crosstalk between the cell constituents within the TME. Colony-stimulating factor 1 (CSF-1) is secreted by breast cancer cells and is the primary cytokine regulating tumour-associated macrophages (TAMs) in TME which provide pro-tumorigenic milieu for tumour progression and metastasis.This study aimed to evaluate the CSF-1 gene expression in invasive breast carcinoma and its association with pathological prognostic parameters.Materials and Methods: This study was a cross-sectional study involving 128 formalin-fixed paraffin-embedded cases diagnosed as invasive breast carcinoma NST.The cancer cells were stained with anti-CSF-1 immunohistochemical antibody, and the staining intensity was evaluated and scored into low (score 0-1) and high expression (score 2-3).Results: Ninety-three cases expressed high CSF-1. High CSF-1 expression was significantly associated with tumour grade (p=0.008). High CSF-1 expression was seen in 58 (79.5%) tumours with histological grade 2 and 29 (72.5%) with histologic grade 3, respectively. High CSF-1 expression was significantly associated with positive HER-2 (40 cases (87%),p=0.007). Conclusion: This research revealed that high CSF-1 expression is associated with poor prognostic parameters. Therefore, evaluation of CSF-1 expression will be a useful prognostic marker and may serve as potential cellular target for novel treatment modality in invasive breast cancers.